Analisis Pengaruh Manajemen Modal Kerja Terhadap Profitabilitas (Studi Kasus Pada Perusahaan Properti dan Real Estate yang Go Public di BEI Tahun 2006 – 2011) - Yuni Sartika Sitorus; Irsutami Irsutami (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2013)
This study aimed to determine the effect of working capital manajemen on independence of profitability. The method used is regression analysis to compare the three variables is average collection period, inventory turnover in days, dan average payment period (independent variable) with the independence of profitability/ROI (dependent variable). Using a sample of 12 property and real estate companies, this study was able to prove that the working capital management significantly negative effect on profitability (ROI).